STUDY ON THE EFFECTS OF CASTICIN AGAINST GENTAMICIN-INDUCED DYSREGULATION OF OXIDATIVE STRESS, MITOCHONDRIA AND SERUM CHEMISTRY IN RATS - Sabahat Shahzadi; Muhammad Umar Ijaz; Muhammad Imran; Huma Naz; Shabab Nasir; Rao Zahid Abbas; Sidra Altaf (Journal of Animal and Plant Sciences, 2023)
Gentamicin (GM) is an important aminoglycoside antibiotic to treat different infections caused by gram-negative bacteria. Mitochondrial dysfunction is considered as a key factor in the pathogenesis of renal disorders, and an important consequence of GM-induced nephrotoxicity that results in structural and functional alteration. Casticin (CAS) is a potential phytochemical having various pharmacological properties. The current investigation was formulated to ascertain the protective effects of CAS on GM induced mitochondrial dysfunction in kidney of rats. For this study, mature Sprague Dawley rats (n=48), weighing 200 ± 20g were used and divided into four groups (n=12) using a completely randomized design (CRD); Group 1 (control group), Group 2 (GM dose, 80 mgkg-1 b. wt i.p), Group 3 (80 mg/kg GM (i.p) and 50 mgkg-1 b.wt of CAS orally) and Group 4 (CAS 50 mgkg-1 b.wt orally). All rats were treated for ten days continuously. Our finding showed that GM administration significantly increased the concentration of urea and creatinine; however, creatinine clearance was reduced. GM treatment increased the level of mitochondrial reactive oxygen species (ROS) and lipid peroxidation, while the activity of glutathione, catalase, superoxide dismutase and glutathione peroxidase were decreased. Mitochondrial tricarboxylic acid (TCA) cycle enzymes (succinate dehydrogenase, isocitrate dehydrogenase, malate dehydrogenase and alpha-ketoglutarate dehydrogenase) activities were decreased after GM exposure. In addition, mitochondrial electron transport chain (ETC) enzymes, i.e., NADH dehydrogenase, succinate-dehydrogenase, succinic-coenzyme Q and cytochrome c-oxidase activities were reduced followed by GM administration. GM administration decreased mitochondrial membrane potential (ΔΨm) while significantly induced histological damage. However, treatment of CAS abrogated the damaging effects of GM in isolated renal mitochondria. Therefore, the present study demonstrated that CAS exhibits palliative effects against GM-induced renal mitochondrial impairment in the rats.
Keywords: Gentamicin; Mitochondrial dysfunction; Kidney; Casticin; Antioxidant enzymes